Harnessing mRNA vaccines for viral diseases: bottleneck and breakthrough - Vijay Mishra; Abhigyan Ranjan; Yachana Mishra (Exploration of Immunology)
Messenger RNA (mRNA) vaccines represent a novel category of vaccinations with significant potential for the future. Recent studies have demonstrated the effectiveness of mRNA vaccines in combating various viral infections and cancer, particularly in cases where traditional vaccine platforms may not produce protective immune responses. In particular, mRNA vaccines have gained attention due to their quick development, scalable manufacturing, and ability to elicit strong immune responses. This review elucidates the synthesis of mRNA and mRNA vaccines, their mechanisms of action, and the strategies to enhance their delivery and address their advantages and limitations for viral disease. Many delivery strategies have been investigated in recent years, concentrating on nanoparticle-mediated mRNA vaccine delivery. The delivery mechanism is crucial for improving mRNA vaccine stability, biocompatibility, and targeting specific cells and tissues. By preventing mRNA degradation and increasing cellular uptake, nanocarriers significantly contribute to the stability and immunogenicity of mRNA vaccines. Nanoformulation functions not only as a carrier but also as a compartment that safeguards the mRNA from biological, chemical, and physical processes that may compromise its safety and efficacy. Despite these advances, challenges such as long-term safety and innate immune activation remain. Eventually, this review concentrated on future considerations necessary for the more efficient and safer deployment of mRNA, emphasizing the merits and drawbacks of the existing viral disease mRNA vaccines, with an eye toward future innovations and clinical applications.